Study of Extrinsic Apoptotic Pathway in Oral Pemphigus Vulgaris Using TNFR 1 and FasL Immunohistochemical Markers and TUNEL Technique - Parviz Deyhimi; Batoul Alishahi (Journal of Dentistry, 2018)
Statement of the Problem: Pemphigus vulgaris is characterized by intraepithelial vesicles, but pathogenesis of vesicle formation in this disease has not been substantiated yet. Purpose: The present study investigate extrinsic apoptotic pathway in oral pemphigus vulgaris using TUNEL and important immunohistochemical markers of extrinsic pathway, TNFR1 and FasL. Materials and Method: In the present cross sectional study, 25 oral pemphigus vulgaris samples and 6 normal oral mucosa were analyzed for the presence of apoptosis by TUNEL and the staining of TNFR1 and FasL in basal and parabasal layers around vesicle, vesicle floor, vesicle roof and acantholytic cells. The staining expression and intensity were measured and the obtained data were analyzed by Wilcoxon and Mann-Whitney tests. Results: There was no or faint staining of TUNEL, FasL and TNFR1 in normal oral mucosa. In addition, there was no significant difference between the staining of TUNEL technique in different layers. The staining of TNFR1 marker was very high in all regions. FasL marker was not positive in the basal and parabasal layers around vesicle in 92% of samples but showed a varied and different staining in vesicle region. There was a significant difference between the each two markers in all layers (p <0.001). Conclusion: Apoptosis is probably is a preceding phenomenon to acantholysis in pemphigus vulgaris. It appears that the apoptosis occurs mostly by extrinsic pathway using proapototic mediators TNFR1 and FasL.